Modelling of regulatory factor and managerial impact assessment in the regional economy sectors: a case-study of the Kaliningrad region (Russia). Issue 1 (1st January 2019) - Voloshenko, K.; Ponomarev, A.; Naumtseva, I.
Abstract: This article discusses the methodology of developing tools for assessing regulatory factors and managerial impacts on the regional economy and individual sectors and businesses. The potential of projection models is investigated, including balance models, convergence of regional and sectoral projection and compiling reliable and representative data sets capable of describing the current economic situation. An attempt was made to develop a series of models for several regional economies; to that end, the modelling of managerial and regulatory impact assessment was used in combination with the well-known value chain approach. In the interests of effective public administration, one of the requirements is to create sectoral model formats compatible with the regional projection models. Results of pilot modelling managerial and regulatory impacts on Kaliningrad region's economies are presented through examples of agribusiness, transport, industry, tourism and recreation. Implementation of regulatory impact modelling in the framework of the suggested approach is proved for other regions. The main advantage of the developed models for the regional management is their ability to reduce uncertainty in decision-making due to obtaining estimates of the impact of the decisions on the changing situation and the conditions for the development of sectors and industries.